Comparative endothelial profiling of doxorubicin and daunorubicin in cultured endothelial cells. Issue 3 (April 2015) - Wojcik, Tomasz; Buczek, Elzbieta; Majzner, Katarzyna; Kolodziejczyk, Agnieszka; Miszczyk, Justyna; Kaczara, Patrycja; Kwiatek, Wojciech; Baranska, Malgorzata; Szymonski, Marek; Chlopicki, Stefan
<x xml:space="preserve">Abstract</x> Graphical abstract